Reconciling change: 52 Tuesdays - Dooley, Kathleen (Australian Teachers of Media, 2014)
52 Tuesdays is an important film in a number of ways: it's Australian, it employs a groundbreaking approach to filming, and it explores complex emotional issues surrounding gender transition and sexuality. Kath Dooley looks at how these factors play out in Sophie Hyde's award-winning new film.